Combined analysis of neutrino decoherence at reactor experiments - André de Gouvêa; Valentina De Romeri; Christoph A. Ternes (Journal of High Energy Physics)
Abstract Reactor experiments are well suited to probe the possible loss of coherence of neutrino oscillations due to wave-packets separation. We combine data from the short-baseline experiments Daya Bay and the Reactor Experiment for Neutrino Oscillation (RENO) and from the long baseline reactor experiment KamLAND to obtain the best current limit on the reactor antineutrino wave-packet width, σ > 2.1 × 10 −4 nm at 90% CL. We also find that the determination of standard oscillation parameters is robust, i.e., it is mostly insensitive to the presence of hypothetical decoherence effects once one combines the results of the different reactor neutrino experiments.